A systematic review of the neurophysiology of mindfulness on EEG oscillations. (October 2015) - Lomas, Tim; Ivtzan, Itai; Fu, Cynthia H.Y.
Highlights: We conducted a systematic review of EEG studies of mindfulness meditation. We examined power differentials between mindfulness and a control state. Mindfulness was associated with enhanced alpha and theta power. No consistent patterns were observed in terms of beta, delta and gamma. Elevated alpha and theta may signify a state of relaxed alertness. Abstract: Mindfulness meditation has been purported to be a beneficial practice for wellbeing. It would therefore be expected that the neurophysiology of mindfulness would reflect this impact on wellbeing. However, investigations of the effects of mindfulness have generated mixed reports of increases, decreases, as well as no differences in EEG oscillations in comparison with a resting state and a variety of tasks. We have performed a systematic review of EEG studies of mindfulness meditation in order to determine any common effects and to identify factors which may impact on the effects. Databases were reviewed from 1966 to August 2015. Eligibility criteria included empirical quantitative analyses of mindfulness meditation practice and EEG measurements acquired in relation to practice. A total of 56 papers met the eligibility criteria and were included in the systematic review, consisting of a total 1715 subjects: 1358 healthy individuals and 357 individuals with psychiatric diagnoses. Studies were principally examined for power outcomes in each bandwidth, in particular the power differentials between mindfulness and a control state, as well as outcomes relating to hemispheric asymmetry and event-related potentials. The systematic review revealed that mindfulness was most commonly associated with enhanced alpha and theta power as compared to an eyes closed resting state, although such outcomes were not uniformly reported. No consistent patterns were observed with respect to beta, delta and gamma bandwidths. In summary, mindfulness is associated with increased alpha and theta power in both healthy individuals and in patient groups. This co-presence of elevated alpha and theta may signify a state of relaxed alertness which is conducive to mental health.